Argininosuccinate synthase 1 and periportal gene expression in sonic hedgehog hepatocellular adenomas. Issue 3 (6th June 2018) - Nault, Jean‐Charles; Couchy, Gabrielle; Caruso, Stefano; Meunier, Léa; Caruana, Laure; Letouzé, Eric; Rebouissou, Sandra; Paradis, Valérie; Calderaro, Julien; Zucman‐Rossi, Jessica
Abstract : Genetic alterations define different molecular subclasses of hepatocellular adenoma (HCA) linked with risk factors, histology and clinical behavior. Recently, Argininosuccinate Synthase 1 (ASS1), a major periportal protein, was proposed as a marker of HCA with a high risk of hemorrhage. We aimed to assess the significance of ASS1 expression through the scope of the HCA molecular classification. ASS1 expression was evaluated using RNAseq, quantitative reverse transcriptase polymerase chain reaction (RT‐PCR) and Immunohistochemistry. ASS1 and glioma‐associated oncogene 1 (GLI1) expression were analyzed in vitro after modulation of GLI1 expression. Using RNAseq in 27 HCA and five nontumor liver samples, ASS1 expression was highly correlated with GLI1 expression (P<0.0001, R=0.75). In the overall series of 408 HCA, ASS1 overexpression was significantly associated with sonic hedgehog HCA (shHCA) compared to other molecular subgroups (P<0.0001), suggesting that sonic hedgehog signaling controls ASS1 expression. GLI1 expression silencing by siRNA induced a downregulation of ASS1 in PLC/PFR5 and SNU878 cell lines. In 390 HCA, we showed that ASS1 expression belonged to the periportal expression program that was maintained in shHCA but down‐regulated in all the other HCA subtypes. In contrast, HCA with β‐catenin activation showed an activation of a perivenous program. Despite the significant association between GLI1 and ASS1 expression, ASS1 mRNA expression was not associated with specific clinical features. At the protein level using immunohistochemistry, prostaglandin D synthase (PTGDS) was strongly and specifically overexpressed in shHCA. Conclusion : ASS1 is associated with sonic hedgehog activation as part of a periportal program expressed in shHCA, a molecular subgroup defined by INHBE‐GLI1 gene fusion. (Hepatology 2018).